Nic Bishop frogs. - Bishop, Nic, 1955- (New York : Scholastic, 2008)
Full-color, illustrated photographs describing the characteristics and behaviors of a variety of frogs around the world.
Includes index.
Book Links (A.L.A.).
Horn Book Starred.
School Library Journal starred.
3.7
K-3
Keywords: Frogs -- Juvenile literature; Frogs; Frogs